(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Lung cancer is a common malignancy, the leading cause of cancer death worldwide. Caring and treating for lung cancer patients is a process that requires the patient and their family to have perseverance, faith and great efforts both physically and mentally. Objective: Description the quality of life among lung cancer patients after radiation therapy at the National Lung Hospital in 2020. Methods: Cross-sectional study. The study collected information from patients with lung cancer after radiation therapy in the National Lung Hospital through standardized EORTC QLQ-C30 and EORTC QLQ-LC13 questionnaires in Vietnam. The patient’s CLCS was evaluated according to 5 functionals and clinical symptoms. Data were entered by Epidata 3.1 and analyzed by SPSS 18.0. Results and conclusion: The finding showed that, QoL of patients was average (55.1 points), physical function (69.5 points), cognitive function (65.6 points), operational function (62.5 points), emotional function (56.3 points) and social functioning (51.4 points). Common symptoms of patients after radiation therapy include: sleep disturbance (39.8 points), loss of appetite (35.2 points), pain (33.2 points), fatigue (29.4 points), shortness of breath (25.7 points), nausea, constipation (18.6 points) and diarrhea (9.2 points).